Pengaruh Corporate Social Responsibility Terhadap Harga Saham : Kinerja Keuangan Sebagai Variabel Moderasi - Yumita; Yulindisti, Elga; Desyana, Gita (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study is the motivated by the importance of the role of Corporate Social Responsibility (CSR) in maintaining stock price stability, especially in sector which is vulnerable to market fluctuations. The phenomena behind this research is the increasing awareness and attention of the public and investors to corporate social responsibility as part of sustainable business practices and the influence of market perceptions on the company’s reputation. In the context of mining companies, CSR activities are important because this sector has significant environmental and social impacts. The aim is to identify the effect of CSR disclosure with three dimensions, namely economic, environmental, and social on the share price of mining companies listed on the Indonesia Stock Exchange in the period 2020 - 2023, and to analyze the role of financial performance as proxy for ROA as a moderate variable in the relationship. The research method used is quantitative with a purposive sampling and regression data analysis technique using SPSS 25. The results showed that economic CSR has a positive and significant effect on stock prices, while the environmental and social CSR dimensions did not show a significant effect directly. Financial performance proved to be able to moderate the effect of environmental CSR on stock prices, but not on economic and social CSR.